The role of fintech in unlocking green finance: Policy insights for developing countries - Darius Nassiry (Asian Development Bank Institute (ADBI), 2018)
The achievement of the Sustainable Development Goals (SDGs) and implementation of the Paris Agreement will require significant new investment. New financial technologies ("fintech") offer the potential to unlock green finance technologies, such as blockchain, the Internet of Things and big data, developed over the same timeframe as the Paris Agreement and the SDGs. This paper outlines three broad areas for the possible application of fintech to green finance: blockchain applications for sustainable development; blockchain use-cases for renewable energy, decentralized electricity market, carbon credits and climate finance; and innovation in financial instruments, including green bonds. The paper focuses on blockchain use-cases pertaining to sustainable development and renewable energy and highlights examples from Europe, which has been a leader in blockchain technology. The paper explores the implications for developing economies in Asia and draws preliminary recommendations for policy makers interested in harnessing fintech and blockchain for low-carbon, climate-resilient investment and the achievement of the SDGs.
Keywords: O13; O33; O38; Q01; Q54; Q55; Q56; Q58; 330; Green Finance; Fintech; Blockchain